Domical (vitana) ceiling of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The domical (vitana) ceiling of the Mandaleshwar Mahadev Temple is intricately carved. The ceiling is formed of concentric circular rings formed of cusps or fractals. The lowermost ring has brackets with sculptures. The first rings of the ceiling have kirtimukha (face of glory) motifs and a row of small sculptures. The inner rings are made up of semi-circular floral fractals.